ФИЛОСОФСКИЕ ОСНОВАНИЯ ВИЗУАЛИЗАЦИИ И ГРАФИЧЕСКОГО МОДЕЛИРОВАНИЯ В ИССЛЕДОВАНИЯХ МУЗЫКИ - Кобелева, Д. Л. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Статья посвящена проблеме формулировки философских оснований для исследования музыки, в ка-честве которых могут быть использованы концепции Г. В. Лейбница и И. Канта. Основываясь на тео-ретических системах, изложенных в «Монадологии» и «Критике чистого разума», предложена новаятрактовка музыкального тона. Рассмотрен метод теоретического моделирования музыкальной мело-дии с помощью графической визуализации.Кобелєва Д. Л. Філософські підстави візуалізації і графічного моделювання у дослідженняхмузики. Стаття присвячена проблемі формулювання філософських підвалин для дослідження музики, уякості яких можуть бути використані концепції Г. В. Лейбниця та І. Канта. Спираючись на теоретичнісистеми, викладені в «Монадології» та «Критиці чистого розуму», запропонована нова трактовка музи-чного тону. Розглянуто метод теоретичного моделювання мелодії за допомогою графічної візуалізації.Ключові слова: музика, теорія пізнання, візуалізація, мелодична структура, тон.Kobelieva D. L. Philosophical foundations of vizualization and graphical modeling trend in musicalinvestigations. In this paper we consider the problem of the philosophical foundations of music studying. Thistopic is relevant, because the music as multi-faceted phenomenon is studied in the framework of various sciencesand their trends. However, in order to combine the results of these studies together, it is necessary to find some common ground. In our opinion, as such grounds, we should take the philosophical ideas about the possibility ofperception and knowledge of the world in general and music in particular. Thus, the purpose of this article is anattempt to form the philosophical foundations of music studying in a new direction – visualization of melodic relationships,and generalizations of existing results. To realize this idea we turn to the ideas of G. V. Leibniz, thatexpressed in "Monadology", and the concept of I. Kant that expounded in the "Critique of Pure Reason". We definemelody as music-semantic structure and propose a new method for studying music, which is based on thedestruction of this structure. The method is called "relative degradation of semantic structures". It consists in thedestruction of the music and semantic structure relative to itself by exposure to the elements that constitute it, anddirectly on the form factors.Keywords: music, the theory of knowledge, visualization, melodic structure, tone.